2023
DOI: 10.1021/acsomega.3c01401
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Self-Cross-Linking Hydrogels Based on Chitosan Derivatives and Oxidized Sodium Alginate

Abstract: A self-cross-linking and biocompatible hydrogel has wide application potential in the field of tissue engineering. In this work, an easily available, biodegradable, and resilient hydrogel was prepared using a self-cross-linking method. This hydrogel was composed of N-2-hydroxypropyl trimethyl ammonium chloride chitosan (HACC) and oxidized sodium alginate (OSA). A stable and reversible cross-linking network was formed by the Schiff base self-cross-linked and hydrogen bonding. The addition of a shielding agent (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In addition, NaCl weakens the strong electrostatic interaction between collagen and OSA, an anionic polysaccharide. NaCl ions shield the charge of polyelectrolytes in solution, disfavoring the electrostatic interactions, and then, the importance of non-electrostatic forces on OSA-collagen interaction increases [ 64 , 65 ]. The use of a limited, but adequate amount of NaCl is therefore peremptory.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, NaCl weakens the strong electrostatic interaction between collagen and OSA, an anionic polysaccharide. NaCl ions shield the charge of polyelectrolytes in solution, disfavoring the electrostatic interactions, and then, the importance of non-electrostatic forces on OSA-collagen interaction increases [ 64 , 65 ]. The use of a limited, but adequate amount of NaCl is therefore peremptory.…”
Section: Resultsmentioning
confidence: 99%
“…Water is a fundamental component of the collagen hierarchical structure, and several authors have suggested that the short component of the transversal relaxation time is caused by water molecules tightly bound to collagen helices in the interfibrillar space whereas the long component is caused by water molecules bound to microfibrils [64,65,67,68]. As a result, the long component is significantly more mobile, sensitive to the effects of tanning agents, and vulnerable to variations in hydration levels [66] than the short component.…”
Section: H Unilateral Nmr and Ftir-atr Analysis Of Collagen-osa Chemi...mentioning
confidence: 99%
“…Both these properties were due to the ability of borax to form a tetraborate complex with the adjacent hydroxyl groups in ADA. [7] The available aldehyde groups in ADA can form covalent crosslinking with amino groups in gelatin [8,9] and chitosan [10][11][12] or ionic crosslinking in the presence of CaCl 2 , CaCO 3 , CaSO 4, etc. [5,13,14] The addition of borax to the ADA solution also reduces the gelation time.…”
Section: Introductionmentioning
confidence: 99%
“…The rich aldehyde groups of OSA can react with many moieties to form dynamic covalent bonds. For example, Yu et al prepared the hydrogel with high elasticity and compressive deformation resistance (224 kPa) by a self-cross-linking reaction between chitosan derivatives and OSA . Wang et al constructed an injectable, bioresponsive, and self-repairing hydrogel based on OSA and hydrazide-modified polyethylene glycol .…”
Section: Introductionmentioning
confidence: 99%